2000
DOI: 10.1037/0022-006x.68.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of relapse/recurrence in major depression by mindfulness-based cognitive therapy.

Abstract: This study evaluated mindfulness-based cognitive therapy (MBCT), a group intervention designed to train recovered recurrently depressed patients to disengage from dysphoria-activated depressogenic thinking that may mediate relapse/recurrence. Recovered recurrently depressed patients (n = 145) were randomized to continue with treatment as usual or, in addition, to receive MBCT. Relapse/recurrence to major depression was assessed over a 60-week study period. For patients with 3 or more previous episodes of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

75
1,887
19
89

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 2,422 publications
(2,129 citation statements)
references
References 29 publications
75
1,887
19
89
Order By: Relevance
“…The online mindfulness course assessed in this study comprised elements of mindfulness-based stress reduction (MBSR; Kabat-Zinn, 1990) and mindfulness-based cognitive therapy (MBCT; Teasdale, Segal, Williams, Ridgeway, Soulsby, & Lau, 2000). The course is run by the Mental Health Foundation (UK) and Wellmind Media (UK) and was developed in conjunction with leading UK mindfulness instructors (Krusche, Cyhlarova, King, & Williams, 2012).…”
Section: Online Mindfulness Coursementioning
confidence: 99%
“…The online mindfulness course assessed in this study comprised elements of mindfulness-based stress reduction (MBSR; Kabat-Zinn, 1990) and mindfulness-based cognitive therapy (MBCT; Teasdale, Segal, Williams, Ridgeway, Soulsby, & Lau, 2000). The course is run by the Mental Health Foundation (UK) and Wellmind Media (UK) and was developed in conjunction with leading UK mindfulness instructors (Krusche, Cyhlarova, King, & Williams, 2012).…”
Section: Online Mindfulness Coursementioning
confidence: 99%
“…Different kinds of modifications of CBT were found to be effective as well, such as mindfulnessbased cognitive therapy (MBCT) [26][27][28]. MBCT uses conventional methods of CBT which combined with mindfulness meditation.…”
Section: Introductionmentioning
confidence: 99%
“…However, many investigators found that MBCT might not reduce the risk of developing a new relapse of depression in patients with 2 previous episodes [28,32]. Investigators offered two hypotheses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations